SCIENCE CHINA Technological Sciences (Science in China Series E)( Volome 46 Supplement) - EDTORIAL COMMITTEE OF SCIENCE IN CHINA (2003)
Mountain Hazards and Mitigaton 序号 篇名 作者 页码 1 Debris flow prevention pattern in national parks Taking the world natural heritage Jiuzhaigou as an example CUI Peng, LIU Suqing, TANG Bangxing & CHEN Xiaoqing 1-11 2 Risk and size estimation of debris flow caused by storm rainfall in mountain regions CHENG Genwei 12-19 3 Self-organized criticality and its application in the slope disasters under gravity YAO Lingkan, HUANG Yuan & LU Yang 20-30 4 Behavior of pre-stress group anchors——Theory approach and model HE Siming, WANG Chenghua & QIAO Jianping 31-41 5 Research on evolution and prevention of the No.1 large-scale dangerous slope of Erlang Mountain on the Sichuan-Tibet Highway ZHANG Xiaoyan 42-51 6 Rainfall-induced landslide stability analysis in response to transient pore pressure——A case study of natural terrain landslide in Hong Kong LAN Hengxing, ZHOU Chenghu C. F. LeeWANG Sijing & WU Faquan 52-68 7 Synergetic-bifurcated prediction model of slope occurrence and its application HUANG Zhiquan & WANG Sijing 69-77 8 Study on ground temperature change and characteristic response of engineering geology of permafrost along Qinghai-Tibet Railway PAN Weidong, WANG Quancai, YU Shaoshui & ZHANG Xiaoyan 78-90 9 Human activity response and prevention strategies on soil and water loss in Sichuan Province FANG Yiping & CHEN Guojie 91-109 10 Rainfall infiltration on hilly slopes under various lithology and its effect on tree growth in the dry-hot valley YANG Zhong, XIONG Donghong, ZHOU Hongyi & ZHANG Xinbao 110-119 11 General regularity of dynamic responses of slopes under dynamic input QI Shengwen, WU Faquan & SUN Jinzhong 120-132 12 Anti-scourability of purple soil on hillslopes with different land uses ZHANG Jianhui, LIU Gangcai, NI Shijun, ZHU Bo & GE Fanglong 133-141 13 A 3D visible evaluation of landslide risk degree under integration of GIS and artificial intelligence QIAO Jianping, ZHU Axing, CHEN Yongbo& WANG Rongxun 142-147 14 Monitoring on soil erosion and sediment delivery ...